A study on assessing the risk factors, outcomes and antimicrobial sensitivity patterns of surgical site infections (International Journal of Medicine and Medical Sciences, 2019)
A prospective study was carried out on 1125 surgeries for the incidence of surgical site infections (SSIs). The etiologic agent was isolated, identified and the antibiotic susceptibility pattern was determined using standard methods. The risk associated with SSIs was assessed by multivariate regression logistic analysis. A casecontrol study was carried out for the outcome of SSIs. The outcomes measured were: length of intensive care unit (ICU) stay (in days), length of ward stay (in days), costs incurred (in rupees) by the patient, and mortality rate. The results indicated that 12% of patients undergoing surgery developed SSI. Staphylococcus aureus (33%) and Enterococcus spp. (33%) were the commonest etiologic agents. Patients with SSIs had a significantly extended ICU and ward stay (p